Reshaping the work-life balance directive with Covid-19 lessons in mind - Kalina Arabadjieva (European Trade Union Institute (ETUI), 2022)
The Covid-19 pandemic has disproportionately affected women, threatening to reverse progress towards gender equality. It has made the need to address long-standing structural disadvantages affecting women even more evident and pressing, including the fact that women continue to perform a greater share of unpaid care work. This paper argues that the Work-Life Balance Directive 2019 - the key EU legal instrument that seeks to address the labour market disadvantages of those with caring responsibilities, the majority of whom are women - should be revisited in the aftermath of the pandemic. The Directive provides for certain entitlements to leave and flexible working arrangements. The paper proposes how various aspects of the framework could be strengthened in order to promote its gender equality objectives in a more effective and transformative way, and to confer recognition on the social and economic value of unpaid care work. It also points to other key measures that must complement the Directive to ensure a cultural shift towards equal distribution of care work between men and women.
Keywords: 330; Familie-Beruf; Coronavirus; EU-Recht; EU-Staaten